Traffic related air pollution and incidence of childhood asthma: results of the Vesta case-control study. Issue 1 (18th December 2003) - Zmirou, D; Gauvin, S; Pin, I; Momas, I; Sahraoui, F; Just, J; Le Moullec, Y; Brémont, F; Cassadou, S; Reungoat, P; Albertini, M; Lauvergne, N; et al.
Abstract : Study objective: The Vesta project aims to assess the role of traffic related air pollution in the occurrence of childhood asthma. Design and setting: Case-control study conducted in five French metropolitan areas between 1998 and 2000. A set of 217 pairs of matched 4 to 14 years old cases and controls were investigated. An index of lifelong exposure to traffic exhausts was constructed, using retrospective information on traffic density close to all home and school addresses since birth; this index was also calculated for the 0–3 years age period to investigate the effect of early exposures. Main results: Adjusted on environmental tobacco smoke, personal and parental allergy, and several confounders, lifelong exposure was not associated with asthma. In contrast, associations before age of 3 were significant: odds ratios for tertiles 2 and 3 of the exposure index, relative to tertile 1, exhibited a positive trend (1.48 (95%CI = 0.7 to 3.0) and 2.28 (1.1 to 4.6)), with greater odds ratios among subjects with positive skin prick tests. Conclusions: These results suggest that traffic related pollutants might have contributed to the asthma epidemic that has taken place during the past decades among children.